NDZ Analysis of Various Passive Islanding Detection Methods for Integrated DG System over Balanced Islanding - Reddy, Ch Rami; Harinadha Reddy, K (International Journal of Integrated Engineering, 2019)
In this paper different passive islanding detection schemes for synchronous distributed generation (DG) is presented and their performance is evaluated. Renewable DG systems place a vital role in the smart grids. One of the important problems due to such renewable DG system is an unintentional islanding. Islanding is caused if DG  still supplies power to load after disconnecting from the grid. As per the DG interconnection standards, it is required to detect the islanding within 2 seconds after islanding with the equipments connected to it. In this paper different passive islanding detection (ID) methods are compared and their performance is evaluated for wind DG systems. The combined changes of rate of change of positive sequence voltage (ROCOPSV) and current, the rate of change of negative sequence voltage (ROCONSV) and current, rate of change of frequency over reactive power (ROCOFORP) are evaluated as the better methods for islanding detection at low or zero power balanced islanding. The sensitivity analysis of these methods is simulated in MATLAB for different load variations of islanding and non islanding events. The passive methods which work under zero power imbalances with zero non detection zone (NDZ) are finalized. This analysis indicates each method has different sensitivity for islanding and non islanding events.